A biomimetic hyaluronic acid‐silk fibroin nanofiber scaffold promoting regeneration of transected urothelium. Issue 2 (18th November 2021) - Niu, Yuqing; Galluzzi, Massimiliano; Deng, Fuming; Zhao, Zhang; Fu, Ming; Su, Liang; Sun, Weitang; Jia, Wei; Xia, Huimin
Abstract: This study was designed to investigate the regulatory effect of hyaluronic acid (HA)—coating silk fibroin (SF) nanofibers during epithelialization of urinary tract for urethral regeneration. The obtained electrospun biomimetic tubular HA‐SF nanofiber scaffold is composed of a dense inner layer and a porous outer layer in order to mimic adhesion and cavernous layers of the native tissue, respectively. A thin layer of HA‐gel coating was fixed in the inner wall to provide SF nanofibers with a dense and smooth surface nano‐topography and higher hydrophilicity. Compared with pure SF nanofibers, HA‐SF nanofibers significantly promoted the adhesion, growth, and proliferation of primary urothelial cells, and up‐regulate the expression of uroplakin‐3 (terminal differentiation keratin protein in urothelium). Using the New Zealand male rabbit urethral injury model, the scaffold composed of tubular HA‐SF nanofibers could recruit lumen and myoepithelial cells from the adjacent area of the host, rapidly reconstructing the urothelial barrier in the wound area in order to keep the urinary tract unobstructed, thereby promoting luminal epithelialization, smooth muscle bundle structural remodeling, and capillary formation. Overall, the synergistic effects of nano‐topography and biophysical cues in a biomimetic scaffold design for effective endogenous regeneration.